(untitled) (World of finance, 2021)
Introduction. Carrying out economic activity by individuals and legal entities in some cases provided by the production process is accompanied by systematic damage to the environment. The system of “paid pollution” should create conditions for the polluter when he seeks to reduce or completely abandon the negative impact on the environment, and for the state it should be a source of accumulation of funds that will be further aimed at restoring the environment and forming appropriate conditions for the transition to a “green” way of doing business. In this context, an important task is to analyze the current state of the environmental taxation system in Ukraine and develop recommendations for its improvement. The purpose of the article is to identify the problems of collecting environmental tax in Ukraine, using of funds accumulated through environmental taxation and justify the ways to solve existing problems in the context of European integration. Methods. The study used a number of general and special research methods, in particular: analysis, synthesis, generalization and statistical. Results. As a result of the study of the state of environmental taxation in Ukraine, the data on “green” revenues and expenditures of the State Budget of Ukraine are systematized, the structure and dynamics of revenues from various types of environmental payments are analyzed. The experience of ecological taxation in the countries of the European Union is analyzed. The problematic aspects of “green” public finances are outlined and ways to solve them are suggested. Perspectives. Further research should focus on assessing the relationship between environmental and economic policy of the state and economic development in general, to analyze the real and potential risks to business and the population, subject to the implementation of the government’s European integration commitments.